Computational study on molecular structure, vibrational and electronic properties of a novel Schiff base: Benzyl2-(4-(bis(2-chloroethyl)benzylidene) hydrazinecarbodithioate - Bhuvanendra Singh; Rajeev Singh; Bhoop Singh; Dilip Kumar (Kuwait Journal of Science)
The present study reports a novel Schiff base ‘Benzyl2-(4-(bis(2 chloroethyl)amino)benzylidene)hydrazinecarbodithioate’ and its characterization by infra red (IR), nuclear magnetic resonance (NMR), mass spectral methods with its density functional theory (DFT) quantum chemical studies. Tautomerism in this molecule was investigated theoretically by semi-empirical methods. The molecular geometry was calculated by DFT methods using split-valence triple-zeta 6311-G(2d,2p) Pople style basis set. The vibrational frequencies were calculated by DFT method at the same basis set level. The molecular parameters such as highest occupied molecular orbital energy, lowest unoccupied molecular orbital energy, frontier molecular orbital energy gap and dipole moment were calculated by DFT methods using 6311-G(2d,2p) basis set. Molecular electrostatic surface potential and electron localization function plots were also presented. The reactive sites in the molecule studied theoretically with electronic structure in sight.